THE ROLES OF KNOWLEDGE SHARING IN MEDIATING THE EFFECT OF SELF-EFFICACY AND SELF-LEADERSHIP TOWARD INNOVATIVE BEHAVIOR - Widyani, Anak Agung Dwi; Sarmawa, I Wayan Gede; Dewi, I Gusti Ayu Manuati (Jurnal Manajemen dan Kewirausahaan, 2017)
This research is to investigate the correlation between self-efficacy, self-leadership, and knowledge sharing as observed in the innovative behavior of Endek weaving small enterprise in Bali. Innovation is an interesting issue in SMEs, due to its sustainability efforts of the business. Endek weaving is one unique product that has social and economic value. The unit of analysis is Endek weaving small enterprise in Klungkung, a regency located in the east area of Bali, as it is the center production of Endek weaving in Bali area. The number of respondents is 96 employees of Endek weaving companies in Klungkung Regency. Data analysis method in this research is using the quantitative approach with the tool of Structure Equation Model Partial Least Square (SEM PLS). The results show that self-efficacy and self-leadership have significant influences to knowledge sharing. Self-efficacy has an insignificant influence on innovative behavior, while self-leadership has a significant influence on innovative behavior. Knowledge sharing has a significant influence on innovative behavior. An important finding of this research is knowledge sharing as a mediator of self-efficacy to innovative behavior.